2019
DOI: 10.1093/mmy/myz057
|View full text |Cite
|
Sign up to set email alerts
|

Farnesol increases the activity of echinocandins against Candida auris biofilms

Abstract: Candida auris biofilms exhibit decreased susceptibility to echinocandins, which is associated with poorer clinical outcomes. Farnesol is a quorum-sensing molecule enhancing the activity of antifungals; therefore, we evaluated the in vitro effect of farnesol with anidulafungin, caspofungin, or micafungin against biofilms using fractional inhibitory concentration indexes (FICI), Bliss independence model, LIVE/DEAD-assay and scanning electron microscopy. Based on mathematical models, farnesol caused synergism in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 21 publications
0
60
0
Order By: Relevance
“…Fernández-Rivero et al (2017) reported that a supraphysiological farnesol concentration (300 μM) improved the activity of amphotericin B against Candida tropicalis biofilms but did not affect anidulafungin [ 77 ]. Two recent studies by Nagy et al concluded that farnesol significantly enhanced the activity of echinocandins and triazoles against one-day-old C. auris biofilms in vitro, suggesting an alternative approach to overcome the previously well-documented azole and echinocandin resistance of C. auris biofilms [ 45 , 78 ].…”
Section: Farnesolmentioning
confidence: 99%
“…Fernández-Rivero et al (2017) reported that a supraphysiological farnesol concentration (300 μM) improved the activity of amphotericin B against Candida tropicalis biofilms but did not affect anidulafungin [ 77 ]. Two recent studies by Nagy et al concluded that farnesol significantly enhanced the activity of echinocandins and triazoles against one-day-old C. auris biofilms in vitro, suggesting an alternative approach to overcome the previously well-documented azole and echinocandin resistance of C. auris biofilms [ 45 , 78 ].…”
Section: Farnesolmentioning
confidence: 99%
“…Similarly, combinations of azoles with geldamycin were indifferent against the same strains [53]. Furthermore, Nagy and colleagues [55] reported that combinations of farnesol and the three echinocandins approved by the F.D.A. showed positive results against biofilms of C. auris.…”
Section: Alternative Therapies and Clinical Applicabilitymentioning
confidence: 97%
“…Farnesol is a sesquiterpene alcohol quorum-sensing molecule, which works to prevent the formation of C. albicans biofilms. This drug works by inhibiting the support cascade Ras1-cAMP-PKA that acts at the hypha-to-yeast transition [55][56][57]. The synergism mechanism of these drugs is not completely understood; however, farnesol is believed to modulate the expression of genes linked to ergosterol biosynthesis [58].…”
Section: Alternative Therapies and Clinical Applicabilitymentioning
confidence: 99%
See 2 more Smart Citations